Economical and ecological aspects of excise fuels markers system application - Czarnocka, Joanna; Zborowska, Urszula (Studia Ecologiae et Bioethicae, 2009)
This article describes different aspects of tax exemption and fiscal relief for liquid fuels. The common marking system to identify tax fuels was introduced by Directive 95/60/EC. It was explained the aim and the principle of functioning the system of identification of marker fuels.